Bitcoins fundamental value drivers: an empirical analysis - Benner, Tom (2021)
Bitcoin is a decentralized, self-sovereign digital currency that is not controlled by any state, bank, institution or individual. Despite being the best performing asset of the last decade, the technology is still not very well understood and previous literature has shown little consensus about the factors underlying its price formation. This paper aims to enhance the understanding of this new technology and analyze fundamental value drivers. We identified three key valuation models for Bitcoin based on (1)the energy consumption of the network, (2) the level of scarcity of the asset, and (3) the interplay between supply & demand for the digital currency.